(untitled) - Chorafas, D. N. (New York, 1968)
This book is mainly concerned with Continental Europe, Scandinavia, and the U.S.A, but the special problems of Middle East and the developing territories are also discussed.
Keywords: Chảy máu chất xám,Brain drain; Châu Âu,Europe